The new Micro‐set for Adsorptive Stripping Voltammetric Simultaneous Determination of Nickel and Cobalt Traces in Aqueous Media. Issue 9 (6th June 2019) - Ochab, Mateusz; Gęca, Iwona; Korolczuk, Mieczyslaw
Abstract: This article the first reports on a fabrication and application of an electrochemical three electrode micro‐set containing: in situ plated lead film on carbon fiber working microelectrode, Ag/AgCl reference electrode and a platinum wire counter electrode placed in one casing for simultaneous Ni(II) and Co(II) traces determination by square wave adsorptive stripping voltammetry (SW AdSV). Ni(II) and Co(II) in forms of their complexes with nioxime were accumulated on the lead film plated on a carbon fibers microelectrode during standard procedure of measurement. Thanks to the fact that measurements were performed in micro‐vessel of a volume of 200 μl small amounts of reagents were used to prepare samples for measurements. In addition, because of the use of microelectrode, sample solutions were not mixed during accumulation step of measurements. This fact creates the possibility of conducting fields analysis. The experimental parameters (composition of the supporting electrolyte, potential and time of accumulation) and possible interference effects were investigated. The linear calibration graphs for Ni(II) and Co(II) were in the range from 2×10 −9 to 1×10 −7  mol L −1 and from 2×10 −10 to 1×10 −8  mol L −1 for Ni(II) and Co(II), respectively. The correctness of the proposed method was checked by determining Ni(II) and Co(II) in the certified reference material (SPS‐SW1) with satisfactory results. Abstract :